Elevational gradients in the neotropical table mountains: patterns of endemism and implications for conservation. Issue 7 (4th December 2012) - Nogué, Sandra; Rull, Valentí; Vegas‐Vilarrúbia, Teresa; Loyola, Rafael
Abstract Aim The aim of the present study was to describe the diversity patterns along elevational gradients that are crucial for conservation management and for understanding diversification processes in montane environments. This article analyses the distributional range and elevation patterns of endemic and non‐endemic (NE) vascular plants living on a unique set of Neotropical table mountains (tepuis). To investigate the potential causes of the high degree of diversity and endemism we tested the role of elevation, area and the mid‐domain effect (MDE). We also aimed to discuss the origin of the current tepuian biota. Location The Guayana Highlands (northern South America). Emphasis is placed on the mountaintops above 1500 m elevation, which form the highly biodiverse Pantepui biogeographical province. Methods We examined the distribution patterns of vascular plant species richness in relation to elevation, area, and the MDE using generalized additive models. We used Range Model for the MDE. Results We found that regional endemics richness show a hump‐shaped curve in relation to elevation. Single‐tepui endemics (STE) increase with elevation, whereas NE and total species richness decrease. Area and MDE influence this pattern for Pantepui and STE, but not for NE. We also observed that the spatial distribution of endemic richness displays a left‐skewed distribution pattern due to the dominance of STE. Main conclusions Our results demonstrate that a combination of elevation, area and MDE provide a basic explanation for the diversity of vascular plants in Pantepui. In addition, the present study indicates that maxima of STE are located at the highest altitudes, where the possibility of biotic connection (via migration) and gene flux has been minimal, even during glacial phases when most migration pathways amongst the tepui mountains were open. We also suggest that climatic filtering due to the extreme conditions atop the tepuis and low dispersal capacity stand out as the main drivers of the decline in NE species richness with elevation.